Efektivitas Model Penerimaan Teknologi, Inovasi Pribadi Dan Kontrol Perilaku Terhadap Minat Beli Online Shopee - Sinta Nur Sa'idah; Alshaf Pebrianggara; Muhammad Yani (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research examines the influence of the Technology Acceptance Model, Personal Innovation, and Behavioral Control on Shopee Online Buying Interest. Using a quantitative study approach and SmartPLS software, data was obtained from 96 Shopee platform users through a questionnaire. This data shows that each component of the Technology Acceptance Model, namely Personal Innovation and Behavioral Control, has a positive relationship with Online Buying Interest. The findings of this research emphasize the relevance of the technology acceptance model on the Shopee platform, consumer personal innovation, and the implementation of effective behavioral control to increase consumer buying interest on the Shopee site. The findings of this study help researchers develop techniques to increase client engagement and satisfaction when shopping for products or services online. Keywords : Technology Acceptance Model, Personal Innovation, Behavioral Control, Online Buying Interest